A spotlight on alirocumab in high cardiovascular risk patients with type 2 diabetes and mixed dyslipidemia: a review on the emerging data - Rana K; Reid J; Rosenwasser JN; Lewis T; Sheikh-Ali M; Choksi RR; Goldfaden RF (Diabetes, Metabolic Syndrome and Obesity, 2019)
Khyatiben Rana,1 Jessica Reid,1 Joshua N Rosenwasser,2 Todd Lewis,3 Mae Sheikh-Ali,4 Rushab R Choksi,1 Rebecca F Goldfaden1 1East Coast Institute for Research, Jacksonville, FL, USA; 2Lincoln Medical and Mental Health Center, Bronx, NY, USA; 3Baker-Gilmour Cardiovascular Institute, Jacksonville, FL, USA; 4Northeast Florida Endocrine and Diabetes Associates, Jacksonville, FL, USACorrespondence: Rebecca F GoldfadenEast Coast Institute for Research, Jacksonville, FL, USATel +1 904 854 1354Fax +1 904 854 1355Email Rebecca.Goldfaden@ecirmed.comAbstract: Diabetes is a significant and independent risk factor for atherosclerotic cardiovascular disease (ASCVD), leading to morbidity and mortality among this population. The prevention of macrovascular complications, such as CVD, peripheral arterial disease, and cerebrovascular accident, in patients with diabetes is obtained through multifactorial risk reduction, including mixed dyslipidemia management and adequate glycemic control. For patients with diabetes, it is crucial to initiate adequate dyslipidemia therapy to achieve recommended low-density lipoprotein cholesterol (LDL-C) goal of <70 mg/dL or target non-high-density lipoprotein goal of <100 mg/dL. Lipid-lowering therapies (LLTs), such as statins and ezetimibe, are the cornerstone for plasma LDL-C lowering; however, individuals with diabetes are often unable to achieve target lipid goals with these therapies alone and frequently require additional treatments. A new class of LLTs, proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors, provides a novel approach to lowering lipids in persons with high CV risk, such as those with diabetes. The clinical data presented in this review indicate the potential benefits of alirocumab in patients with diabetes and its value as a treatment option in patients with diabetic dyslipidemia with no significant safety concerns.Keywords: praluent, alirocumab, PCSK9, PCSK9 inhibitor, cardiovascular disease, atherosclerosis, dyslipidemia